2010
DOI: 10.1177/112070001002000418
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Technique for Reconstruction of the Femoral Neck in Paediatric Patients

Abstract: Hip deformities during early childhood following Perthes' disease, congenital dislocation or septic arthritis are not rare, causing limitation of motion and limping. A number of proximal femoral osteotomies to address residual deformities have been described, but the outcome has been variable. We describe a proximal femoral osteotomy aimed at restoring a more anatomic insertion of the gluteus medius. The clinical and radiographic results thus far are promising. We believe that the technique improves both the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The mean duration of follow-up in nine of these studies was 74 months (range 6 months to 192 month), and two articles did not mention the duration of follow-up. 11,15 In seven studies, triple osteotomies introduced by Morscher were applied 12,[15][16][17][18][19][20] and four studies reported results of double proximal femoral osteotomies. [9][10][11]21 Overall, 143 patients were included, of whom six underwent bilateral osteotomies (149 hips).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean duration of follow-up in nine of these studies was 74 months (range 6 months to 192 month), and two articles did not mention the duration of follow-up. 11,15 In seven studies, triple osteotomies introduced by Morscher were applied 12,[15][16][17][18][19][20] and four studies reported results of double proximal femoral osteotomies. [9][10][11]21 Overall, 143 patients were included, of whom six underwent bilateral osteotomies (149 hips).…”
Section: Resultsmentioning
confidence: 99%
“…11,15 In seven studies, triple osteotomies introduced by Morscher were applied 12,[15][16][17][18][19][20] and four studies reported results of double proximal femoral osteotomies. [9][10][11]21 Overall, 143 patients were included, of whom six underwent bilateral osteotomies (149 hips). Demographic data are demonstrated in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations